Tracheal stent in the treatment of tracheal stenosis - Dipak, S.; Prepageran, Narayanan; Rahmat, O.; Raman, R. (Malaysian Medical Association, 2005)
The use of airway stents for the treatment of benign airway stenosis is increasingly advocated. However, the long-term safety and efficiency of these devices has not been established. We present a case of tracheal stenosis. which persisted despite open surgical and laser correction. The patient required tracheal stent insertion and is currently well with no respiratory difficulty. The use of metallic or silicon intraluminal stent remains appropriate in cases in which there is defined and relative short-term end point of treatment.